Membrane Fouling Potentials of an Exoelectrogenic Fouling-Causing Bacterium Cultured With Different External Electron Acceptors - Ishizaki, So; Papry, Rimana Islam; Miyake, Hiroshi; Narita, Yuko; Okabe, Satoshi (Frontiers in Microbiology, 2019)
Integrated microbial fuel cell (MFC) and membrane bioreactor (MBR) systems are a promising cost-effective and energy-saving technology for wastewater treatment. Membrane fouling is still an important issue of such integrated systems in which aeration (oxygen) is replaced with anode electrodes (anodic respiration). Here, we investigated the effect of culture conditions on the membrane fouling potential of fouling-causing bacteria (FCB). In the present study, Klebsiella quasipneumoniae strain S05, which is an exoelectrogenic FCB isolated from a MBR treating municipal wastewater, was cultured with different external electron acceptors (oxygen, nitrate, and solid-state anode electrode). As results, the fouling potential of S05 was lowest when cultured with anode electrode and highest without any external electron acceptor (p<0.05, respectively). The composition of soluble microbial products (SMP) and extracellular polymeric substances (EPS) was also dependent on the type of electron acceptor. Protein and biopolymer contents in SMP were highly correlated with the fouling potential (R2=0.73 and 0.81, respectively). Both the fouling potential and yield of protein and biopolymer production were significantly mitigated by supplying electron acceptors sufficiently regardless of its types. Taken together, the aeration of MBR could be replaced with solid-state anode electrodes without enhancement of membrane fouling, and the anode electrodes must be placed sufficiently to prevent the dead spaces in the integrated reactor.